Representasi Santri Perempuan Dalam Novel Perempuan Berkalung Sorban Karya Abidah El Khalieqy dan Bidadari Bermata Bening Karya Habiburrahman El Shirazy - Yusriyah, Alfiyatul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to describe the representation of the self-concept of a woman who lives in a boarding school environment. The object of study in this research is the novel Perempuan Berkalung Sorban by Abidah El Khalieqy and Bidadari Bermata Bening by Habiburrahman El Shirazy. The method used in presenting the results of the analysis is the qualitative descriptive method. Researchers conducted a literature search of the two manuscripts to collect research data which was then carried out comparative literature. The approach taken is Literary Psychology with Sigmund Freud's self-concept psychoanalysis. The data discussed in this study:  (1) Analysis of the intrinsic elements of the narrative of the two novels (2) Struggle for achievement, (3) Struggle to get the right of true love, (4) Attitude in facing accusations of slander for adultery. The results showed that the characters Nisa in PBS and Ayna in BBB received education and upbringing in a pesantren environment. This encourages her id, ego, and superego to influence her attitudes, actions, and thoughts intelligently, bravely, and critically in facing inner conflicts in her life.